Evidências de validade do inventário portage operacionalizado adaptado para crianças com baixa visão - Quintão, Cassiana Saraiva (Universidade Federal de São Carlos, 2024)
The literature in the area of psychological assessment highlights that the adaptation and validation of instruments is a complex and rigorous process. According to guidelines in the area, the search for evidence of content validity is a very important criterion, as this contributes both to the reliability of the adapted instrument and to the quality of the results in future psychometric studies. That said, the general objective of this thesis was to investigate the evidence of content validity of the Operationalized Portage Inventory Adapted for Children with Low Vision (IPO-BV) and to examine the applicability of the adapted Inventory. The IPO-BV consists of General Instructions, Specific Instructions and 580 items organized into six areas. The presentation of the investigation of the evidence of validity and applicability of the IPO-BV was organized into three different studies. In Study 1, “Content Validity of the Operationalized Portage Inventory Adapted for Children with Low Vision: Analysis of the Contribution of Expert Judges”, the Expert Committee (CE) assessed the content validity of the IPO-BV according to the suggestions of four expert judges in: Low Vision; Child Development; Construction of the Instrument and Application of the IPO. After the acceptance and incorporation of the suggestions indicated by the expert judges, a new version of the IPO-BV was presented. In Study 2, “Assessment by the Target Audience of the Operationalized Portage Inventory Adapted for Children with Low Vision”, six professionals from different areas, who had experience in caring for children with low vision, assessed the comprehensibility of the expressions, terms, tasks, instructions and items of the Inventory. The analysis was performed using the calculation of the Content Validity Index (CVI) for the criteria: clarity; relevance; and relevance/comprehensiveness. Of the 248 items evaluated, 233 presented CVI = 1.00 and 15 of them obtained CVI = 0.83, meeting the minimum score requirement of 0.80 for each item. A single item, in the Cognition area, presented CVI = 0.50 only in the clarity criterion, having obtained a score = 0.83 in the pertinence and relevance/comprehensiveness criteria. This item was reformulated, taking into account the professionals' observations. In Study 3, “Evaluation of the Applicability of the IPO-BV”, a speech therapist, an occupational therapist and a psychologist who treated children with low vision in two medium-sized cities in the interior of Minas Gerais, evaluated the possible facilities and difficulties in understanding the instructions and applying the Inventory. To do so, they applied the instrument to three children with low vision and filled out a form with the IPO-BV Applicability Assessment Protocol. In general, the results were favorable to its applicability. However, the participants' observations contributed to including a warning about the importance of considering the preparation time for the application in the General and Specific Instructions in each area. New studies should be developed to include the investigation of other types of validity and the application of the IPO-BV by professionals with other specialties and trained laypeople, in other regions of the country, expanding the evaluation sample of the instrument and enhancing future analyses of its psychometric properties.
Validity evidence of the operationalized portage inventory adapted for children with low vision
Keywords: Avaliação psicológica; Evidências de validade; Baixa visão; Crianças; Inventário portage operacionalizado; Psychological assessment; Validity evidence; Operationalized portage inventory; Low vision; Children; CIENCIAS HUMANAS::PSICOLOGIA